Performance characteristics of Terminal Blend rubberized asphalt with SBS and polyphosphoric acid. (15th June 2017) - Lin, Peng; Huang, Weidong; Tang, Naipeng; Xiao, Feipeng
Highlights: Comprehensive rheological evaluation of Terminal Blend hybrid asphalt. Additional SBS polymer led to formation of cross-linked network in TB binder. Further addition of PPA hinder the formation of cross-linked network. TB binder has advantage in inhibiting the formation of carbonyl and sulphoxides. TB + SBS asphalt mixture has good rutting resistance and fatigue performance. Abstract: Terminal Blend (TB) rubberized asphalt is a promising technology in producing crumb rubber asphalt as it overcomes the shortcomings such as lack of storage stability and workability. However, the limitation of TB asphalt is that the high temperature property is drastically reduced compared to conventional rubberized asphalt binders due to the degradation of crumb rubber. Currently, the studies regarding to modification to improve its high temperature property is not adequate. The objective of this paper is to investigate the optimum modification formula of asphalt binders using styrene-butadienestyrene (SBS) and polyphosphoric acid (PPA) and explore their mechanism of modification. Firstly, dynamic shear rheometer (DSR) test and bending beam rheometer (BBR) test were conducted to evaluate the rheological properties at both high and low temperatures. Furthermore, Fourier transform infrared spectroscopy (FTIR) and gel permeation chromatography (GPC) test were conducted to detect the chemical changes of TB modified asphalt binders. Finally, the high temperature stability and fatigue property of TB modified asphalt mixtures were applied to verify the performance properties. Results indicates that 20T3S (20 wt% crumb rubber and 3 wt% SBS) used to produce the modified binders was the best modification formula considering both high and low temperature rheological properties. The modification mechanism was that SBS formed 3D cross-linking network structure in TB binder, which played an important role in enhancing high temperature properties of TB binders. Additionally, 20T3S asphalt mixture had better high temperature stability and fatigue performance comparing to 4.5S (4.5 wt% SBS) modified asphalt mixture.